Effect of a dynamic loaded warm-up on vertical jump performance - de la Cruz Campos, A.; Rojas Ruiz, F. J.; de la Cruz Márquez, J. C.; de la Cruz Campos, J. C.; Cueto Martin, B.; Padial Ruz, R. (European Journal of Human Movement, 2017)
Introduction: The purpose of this study was to determine if an aerobic warm carried out on a cycle ergometer had influence on vertical jump performance. Material and Methods: Participants: 25 football players males (2nd B, IV. Spanish Football League; age 22.7±3.3 years; height 178.8±3.9 cm, mass 75.3±6.8 kg) The warming-up consisted of pedalling for 5 minutes at 114.8±8.3 hr with a power intensity of 112.2±13.2 w, followed by 5 minutes at 147.2±6.7 hr (X=197.5±38.4 w).Pre and post-test was carried out in successive days: 1 st5 day: 5 without countermovement vertical jumps (VJ1); 2 nd day:10 seconds repeated VJ 2 and third day: 60 seconds VJ 3. Heart rate was measured while performing and at recovery. Results: In VJ1, the height went from 41.9±5.4 cm in the pre-test to 43.9±5.8 in the post-test; (F=806.0; p=0.001), the flight increased in time (492.21±45.7 ms vs 508.3547.5 ms p= 0.001), the contact with the ground decreased (217.4 ±46.5 ms vs 211.2±23.6 ms p=0.001) and the maximum heart rate raised 111.2±22.1 hr vs 130.0±13.8 hr. In VJ2 the height implies the jump went from 24.9±5.3cm to 25.0±4.9cm (F=329.3; p <0.001). In VJ3 the height shows the jump time went from 21.1±4.5cm to 21.3±4.2 (F=328.2; p <0.001). The number of jumps in VJ2 went from 15.7±1.7 to 15.6±0.9 (p <0.01) and in VJ3 from 97.5±6.6 to 96.6±7.2 (p <0.01). Conclusion: Two phases of 5 minute warm-ups on a cycle ergometer improves both the vertical jump performance and the heart rate throughout the process.